Perancangan Instalasi Penangkal Petir Eksternal Untuk Gedung Bertingkat Tiga Sekolah Islam Inayah - Mitratul Qhuaris; Azriyenni Azhari Zakri; Fri Murdia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Lightning protection systems are indispensable for buildings that have very vital functions, such as schools. The three-storey building of inayah Islamic school is a place of teaching and learning process that has an area (p x l x t) 39 m x 24 m x 11.2 m. To protect the building from direct and indirect lightning strikes, an external lightning rod is required. This design uses The Volume Collection Method and Rolling Ball Method which is tailored to puipp requirement standards. The calculation result using a collection volume method with angle 0 and peak current of 60 kA obtained a strike distance value of 118,903 m, protection radius value of 70,152 m, collection volume of 1106685,131 m3 and protection angle of 80.39. For the Ball rolling method, the determination of the value of the radius of the ball was determined using the researchers' equations Wagner, Brown &Whitehead, and Anderson & IEEE 1985. The down conductor value is obtained for the Collection Volume method of 7,027 m2 and the Rolling Ball method of 11.71 m2. The earthing systems of both methods both produce 4,098 ohm prisoners for the use of one electrode and 3,321 ohms for the use of two electrodes. Keywords: Lightning strike, Collection Volume Method, Rolling Sphere Metho